2018
DOI: 10.24875/ric.17002335
|View full text |Cite
|
Sign up to set email alerts
|

Innate Immunity in Coronary Disease. The Role of Interleukin-12 Cytokine Family in Atherosclerosis

Abstract: Atherosclerosis is a chronic, progressive, and multifactorial disease modulated by genetic and environmental factors. In recent years, the paradigm that explained atherosclerosis as resulting from a complex interaction between factors not accessible to medical intervention, and modifiable risk factors has changed. In this paradigm, alterations in lipid metabolism were the pivotal concept of atherosclerosis as a chronic degenerative disease. In the last years, an increasing number of observations have shown tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 128 publications
(158 reference statements)
0
18
0
Order By: Relevance
“…The determination of cytokines in the serum of tumor-bearing nude mice can reflect the antitumor mechanism of various tripterine treatments. It is well known that IFN-γ, IL-2, and IL-12A are capable of inhibiting tumor cell proliferation, blocking the angiogenesis pathway, regulating immunity, and decreasing the formation of tumor-associated fibroblasts (TAFs) (Mumm et al., 2011 ; Bunimovich-Mendrazitsky et al., 2016 ; Komohara et al., 2016 ; Yue et al., 2016 ; Jiang et al., 2017 ; Vourc’h et al., 2017 ; Wu et al., 2017 ; Ayuthaya et al., 2018 ; Burkart et al., 2018 ; Hydes et al., 2018 ; Kamensek et al., 2018 ; Lampreht Tratar et al., 2018 ; Posadassánchez & Vargasalarcón, 2018 ). In contrast, IL-10, IL-6, CCl2, TNF-α, and TGF-β are considered to be tumor-promoting cytokines, which could promote the proliferation of tumor cells, rebuilding of vascular networks, and so on (Alhamarneh et al., 2015 ; Song et al., 2015 ; Lau et al., 2016 ; Suchal et al., 2016 ; Kim et al., 2017 ; Kong et al., 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…The determination of cytokines in the serum of tumor-bearing nude mice can reflect the antitumor mechanism of various tripterine treatments. It is well known that IFN-γ, IL-2, and IL-12A are capable of inhibiting tumor cell proliferation, blocking the angiogenesis pathway, regulating immunity, and decreasing the formation of tumor-associated fibroblasts (TAFs) (Mumm et al., 2011 ; Bunimovich-Mendrazitsky et al., 2016 ; Komohara et al., 2016 ; Yue et al., 2016 ; Jiang et al., 2017 ; Vourc’h et al., 2017 ; Wu et al., 2017 ; Ayuthaya et al., 2018 ; Burkart et al., 2018 ; Hydes et al., 2018 ; Kamensek et al., 2018 ; Lampreht Tratar et al., 2018 ; Posadassánchez & Vargasalarcón, 2018 ). In contrast, IL-10, IL-6, CCl2, TNF-α, and TGF-β are considered to be tumor-promoting cytokines, which could promote the proliferation of tumor cells, rebuilding of vascular networks, and so on (Alhamarneh et al., 2015 ; Song et al., 2015 ; Lau et al., 2016 ; Suchal et al., 2016 ; Kim et al., 2017 ; Kong et al., 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Predominantly expressed by macrophages and monocytes, IL-12 is also produced by DCs [6]. Recognized as a major regulator of adaptive type 1 cell-mediated immunity, this phagocyte-produced cytokine binds to naive CD4 + T cells and promotes the generation of proinflammatory Th1 cells, but antagonizes Th2 responses to have a negative impact upon T reg cells [76]. Significant expression of the IL-12 transcript and protein has already been identified in the atherosclerotic plaques of human samples [76].…”
Section: Il-12mentioning
confidence: 99%
“…Recognized as a major regulator of adaptive type 1 cell-mediated immunity, this phagocyte-produced cytokine binds to naive CD4 + T cells and promotes the generation of proinflammatory Th1 cells, but antagonizes Th2 responses to have a negative impact upon T reg cells [76]. Significant expression of the IL-12 transcript and protein has already been identified in the atherosclerotic plaques of human samples [76]. IL-12 was proved to be a proatherogenic molecule in ApoE −/− /IL-12 −/− mouse models due to the smaller size of atherosclerotic lesions in the absence of this cytokine than in its presence [77].…”
Section: Il-12mentioning
confidence: 99%
See 1 more Smart Citation
“…The biological effect mediated by IL-12 is closely associated with signal transducer and activator of transcription (STAT) signaling, specifically STAT4 [15,16]. IL-12 has been identified as an important inflammationrelated cytokine involved in the regulation of several cardiovascular diseases, including myocardial infarction [17], atherosclerosis [18], and hypertension [19]. Recent studies have demonstrated that IL12p40 deficiency accelerates pathological matrix remodeling and promotes the development of AAA [20,21].…”
Section: Introductionmentioning
confidence: 99%